Preliminary results on Siberian sterlet (Acipenser ruthenus marsiglii) fries rearing under intensive conditions - Feledi, Tibor; Rónyai, András (Acta Agraria Debreceniensis, 2013)
In our experiments production performances of Siberian sterlet were tested under intensive tank conditions. During the 25 days long experiment effectiveness of weaning to artificial diet of the fish was investigated. Production performances of fish fed on exclusively dry diet from the beginnings were lower than the other two groups. Between the values of sterlets fed on live food also then suddenly vs. continuously were weaned to dry diet there were no significant differences. Based on our results live food feeding could be suggested for the Siberian sterlet larvae for some days but the method of the weaning to dry diet has no significant influence to the production performances. In 21 days long experiment four different feeding frequencies were tested in Siberian sterlet ( 13 g) fingerlings. Dry feed was offered for the fish continuously, 2, 3 and 4 times per day. There were no significant differences between the values of the four treatments. Based on our results there is no high influence of feeding frequency in case of this size group of Siberian sterlet. During the nursing in two different size groups of Siberian sterlet the optimal daily amounts of feed were aimed to determine. In case of growth values of the group fed at 7% of the total biomass were higher than the other two groups (3 and 5%). Feeding performances of fish fed at 5% were significantly better than fish fed at 7%. Based on our results for 20 g size of the subspecies at least 5% of total body weight could be suggested. In case of 150 g size of the fish the production performances of fish fed at 1% were lower than the other two groups (2 and 3%). Between the values of stocks fed at 2 and 3% there were no significant differences. Based on these results 2% of total body weight of dry feed could be suggested for the Siberian sterlet with 150 g body weight.